Translation Technique of Primary School Teacher Education Department Graduate Students’ Abstracts Final Project - Eka Fanti Sulistiyaningsih; Zaenul Wafa (Journalistics: Journal of English Teaching and Applied Linguistics, 2022)
This research is conducted in order to find out what type and the most dominant of translation techniques that used in primary school teacher education department graduate students’ abstracts final project. This research was applied descriptive qualitative method. The subjects of this research were the final project abstract of students in primary school teacher education department. The data of this research was collected by identifying and classifying. The results of the research shows that, there are three types of translation technique used in their abstract. They are literal translation, calque, and borrowing. The translation techniques are categorized into three categories, they are Literal Translation (52 occurrences or 49,52 %), Borrowing (39 occurrences or 37,14 %), and Calque (14 occurrences or 13,33 %). The first most dominant type of translation technique is Literal Translation. It is for about 52 literal translation and the percentage is 49,52%.